Higher FORTA (Fit fOR The Aged) scores are associated with poor functional outcomes, dementia, and mortality in older people: pharmacoepidemiology and prescreption - Pazan, Farhad; Breunig, Hanna; Weiß, Christel; Röhr, Susanne; Luppa, Melanie; Pentzek, Michael; Bickel, Horst; Weeg, Dagmar; Weyerer, Siegfried; Wiese, Birgitt; König, Hans-Helmut; Brettschneider, Christian; et al. (European journal of clinical pharmacology, 2022)
Purpose: Higher Fit fOR The Aged (FORTA) scores have been shown to be negatively associated with adverse clinical outcomes in older hospitalized patients. This has not been evaluated in other health care settings. The aim of this study was to examine the association of the FORTA score with relevant outcomes in the prospective AgeCoDe-AgeQualiDe cohort of community-dwelling older people. In particular, the longitudinal relation between the FORTA score and mortality and the incidence of dementia was evaluated. Methods: Univariate and multivariate correlations between the FORTA score and activities of daily living (ADL) or instrumental activities of daily living (IADL) as well as comparisons between high vs. low FORTA scores were conducted. Results: The FORTA score was significantly correlated with ADL/IADL at baseline and at all follow-up visits (p < 0.0001). ADL/IADL results of participants with a low FORTA score were significantly better than in those with high FORTA scores (p < 0.0001). The FORTA score was also significantly (p < 0.0001) correlated with ADL/IADL in the multivariate analysis. Moreover, the mean FORTA scores of participants with dementia were significantly higher (p < 0.0001) than in those without dementia at follow-up visits 6 through 9. The mean FORTA scores of participants who died were significantly higher than those of survivors at follow-up visits 7 (p < 0.05), 8 (p < 0.001), and 9 (p < 0.001). Conclusion: In this study, an association between higher FORTA scores and ADL as well as IADL was demonstrated in community-dwelling older adults. Besides, higher FORTA scores appear to be linked to a higher incidence of dementia and even mortality.
Gesehen am 24.07.2023